Final answer:
Solving the equation 5m+4=7m+6 involves moving all m terms to one side and constants to the other, leading to the solution m = -1.
Step-by-step explanation:
To solve the equation 5m+4=7m+6, you need to manipulate the terms in a way that all the terms involving 'm' are on one side and the constant terms are on the other side. This is a process often referred to as collecting like terms. Here are the steps we'll use to find the solution:
Subtract 7m from both sides to get m on one side: 5m - 7m + 4 = 6.
Simplify the equation: -2m + 4 = 6.
Subtract 4 from both sides to isolate the term with m: -2m = 2.
Finally, divide both sides by -2 to solve for m: m = -1.
Thus, the solution to the equation is m = -1.